Avaliação quantitativa e qualitativa de monócitos em pacientes com diabetes mellitus gestacional - Angelo, Ana Geisa Santos de [UNIFESP] (2017)
Introduction: Immunological changes leading to a predominantly inflammatory profile seem to be involved in the pathophysiology of Gestational Diabetes Mellitus (GDM). The role of monocytes and their mediators in this process remains unclear. Objective: The aim of this study was to evaluate the profile of peripheral blood monocytes of patients with GDM and compare it with the observed in healthy pregnant and nonpregnant women. We quantified and evaluated the expression of TLR-4, chemokine CCR2 and cytokines (TNF-A, IL-6 and IL-10) in circulating monocytes of pregnant women with and without DMG and healthy nonpregnant women. Methods: This was a cross-sectional analytical study. Patients were enrolled in the 3 rd trimester of pregnancy, healthy and with GDM, and a group of healthy non-pregnant women. Peripheral blood was collected for quantitative evaluation of total monocytes and their subclasses, and also to characterize their spontaneous and post-stimulation by lipopolysaccharide (LPS) expression of TLR-4, CCR2 and cytokines. All participants underwent oral glucose tolerance test with 75g (TTOG) by the 20th week of gestation, and the diagnosis of GDM was established according to the IADPSG criteria. The percentages of total (CD14+ ), classic (CD14+CD16- ), intermediate (CD14+CD16+ ) and non-classical (CD14+CD16++) monocytes were assessed by flow cytometry. The same technique was used to evaluate the spontaneous and post-stimulation by LPS expression of TLR-4, CCR2, TNF-A + , IL-6 + and IL-10+ in all subclasses. Student t tests, One-Way ANOVA, Kruskal-Wallis, χ2, Pearson's correlation were used for statistical analysis. The level of significance was set at p<0.05. Results: Thirty-eight patients in the third trimester of pregnancy, 20 healthy and 18 patients with GDM, in addition to 18 non-pregnant women of reproductive age were included. The control xviii and DMG groups presented lower number of total CD14+ monocytes when compared to the non-pregnant group, both spontaneous (6,30 +/- 2,37 x 6,67 +/- 1,81 X 11,95 +/- 4,07, respectively, p <0,0001 - One-way ANOVA test) and after stimulation with LPS (Med: 5,37 x 5,24 x 9,74, Iq: 4,33 - 6,29 x 3,88 - 7,15 x 6,38 - 11,78 respectively, p=0,0005 - Kruskal-Wallis test). We did not observe statistically significant difference between the study groups when we analyzed the subsets of monocytes (classic, intermediate and nonclassical) in both situations: spontaneous production or stimulation with LPS. We observed lower expression of TLR-4 by classic monocytes of DMG patients, in comparison to the control and nonpregnant groups (Med: 39,40 x 71,65 x 63,30, Iq: 11,33 - 69,83 x 61,80 - 76,78 x 21,50 - 74,23 respectively, p=0,01 - Kruskal-Wallis test). The same occurred in the intermediate monocytes (Med: 84,25 x 100,00 x 100,00, Iq: 56,10 - 100,00 x 87,00 - 100,00 x 87,50 - 100,00 respectively, p = 0,04 - Kruskal-Wallis test) and, although it was not statistically significant in nonclassical monocytes, we also observed a tendency to lower expression of TLR-4 in the diabetic group (Med: 88,70 x 100,00 x 100,00, Iq: 55,55 - 100,00 x 88,03 - 100,00 x 86,10 - 100,00 respectively, p = 0,08 - KruskalWallis test). We also identified lower levels of sCD14 + in the control group when compared to DMG and non - pregnant groups (Med: 225,50 x 779,20 x 1383,00, Iq: 152,90 - 274,90 x 229,80 - 1623, 00 x 836,70 - 1658,00, respectively, p <0,0001 - Kruskal-Wallis test). As expected, we detected altered laboratory parameters in diabetic pregnant women (glycated hemoglobin: 5,72 +/- 0,33 x 5,32 +/- 0,41 x 5,33 +/- 0,31, respectively, p <0 , 0001 - One-way ANOVA test; fasting glycemia 89,60 +/- 5,55 x 81,52 +/- 8,64, p = 0,001 - Student's t-test). There was no correlation between percentages of CD14 + cells and levels of glycated hemoglobin and fasting glycemia. Conclusion: Patients with DMG had xix lower percentage of monocytes that spontaneously expressed TLR-4. Pregnant women with and without DMG had a lower percentage of total monocytes (CD14+ ) and of monocytes expressing IL-10+ than non-pregnant women.